The good garden : how one family went from hunger to having enough - Milway, Katie Smith, 1960-; Daigneault, Sylvie (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2010)
Eleven-year-old Maria Luz and her family have a small farm in Honduras, but may not have enough food to sustain them for the year, so Maria's father must leave home to find work, leaving her in charge of the garden.
Wilson's Children, September 2011
School Library Journal, October 2010
Book Links (A.L.A.), January 2011
Publisher's Weekly, October 2010
Booklist, November 2010
Horn Book, May 2011
Keywords: Food security -- Honduras -- Juvenile fiction; Agriculture -- Honduras -- Juvenile fiction; Food security -- Fiction; Agriculture -- Fiction; Honduras -- Fiction; Food supply -- Fiction; Agriculture -- Fiction; Honduras -- Fiction